Involvement of the Anglican Church in Nation Building and Political Development in Nigeria - Adetunmbi, Moses Adebolu; Adeleke, Olujobi Adeyemo; Iortyom, Mbazendan; Adejuwon, James Ayoola; Oluwajana, John; Olakanmi, John; Omoyayi, Samuel Olayinka (International Journal of Management and Business Intelligence, 2024)
The Anglican Church in Nigeria has a rich history spanning over 180 years. Here is a brief overview of its journey during this time: In 1842, the first Anglican missionaries arrived in Badagry, Nigeria, which was then a British colony. The study depended on secondary sources of data information and its findings influenced the study conclusion and study recommendation.